The effect of core nodes of geographical identity on psychological stress in network analysis - Lei Zhang; Yang Wang; Haibo Yang (BMC Psychiatry)
Abstract Background Previous research indicates that geographical identity influences psychological stress. However, there is a paucity of explanations for this relationship that considers a diverse range of influencing factors. As a critical component of higher education, university students are exposed to increasing competition and various pressures, which contribute to the widespread issue of psychological stress. Psychological stress is shaped by multiple factors, including geographical identity, interpersonal relationships, and adaptability. Examining the relationship between geographical identity and psychological stress, as well as identifying the core nodes of both, may provide valuable insights into the development of targeted strategies for mitigating psychological stress among university students. Methods This cross-sectional study utilized online surveys to collect data from 1,145 volunteer university students in China. Structural equation modeling and network analysis techniques were employed to analyze the data. Results Geographical identity was found to significantly predict psychological stress (p < 0.05), with adaptability acting as a mediating factor (p < 0.05), and interpersonal relationships serving as a moderating factor (p < 0.05). Interpersonal relationships moderated the relationship between geographical identity and adaptability, weakening the impact of geographical identity on adaptability. Conversely, interpersonal relationships enhanced the effect of adaptability on psychological stress. Additionally, the study found that the core nodes of psychological stress were associated with geographical characteristics (item 17). Notably, there were significant differences in core nodes across academic years and gender groups. Conclusions Strengthening geographical identity and adaptability at the individual level can help alleviate psychological stress, while reducing interpersonal issues in the environmental context may further mitigate stress. Furthermore, university students of different genders and academic years may require tailored approaches for managing psychological stress.